Tracking the Educationalization of the World: Prospects for an emancipated history of education - Daniel Tröhler (Charles University, 2018)
Abstract: Th is article reconstructs the rise, the national diff erentiations and the decline of the genre history of education and outlines subsequently what the history of education could mean if it emancipated itself from the conditions that lead to its emergence, religion and nationalism - conditions, that, nota bene, are by no means as dominant as they once were. Keywords: historiography of education, moralism, nation-building, history of the present